2020
DOI: 10.3390/cells9030751
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role of RUNX2- RUNT Domain in Modulating the Expression of Genes Involved in Bone Metastases: An In Vitro Study with Melanoma Cells

Abstract: Ectopic expression of RUNX2 has been reported in several tumors. In melanoma cells, the RUNT domain of RUNX2 increases cell proliferation and migration. Due to the strong link between RUNX2 and skeletal development, we hypothesized that the RUNT domain may be involved in the modulation of mechanisms associated with melanoma bone metastasis. Therefore, we evaluated the expression of metastatic targets in wild type (WT) and RUNT KO melanoma cells by array and real-time PCR analyses. Western blot, ELISA, immunofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“… 66 RUNT domain promotes bone metastasis of melanoma cells through the complex interactions with genes involved in bone remodeling through the ERK/p-ERK and AKT/p-AKT pathways. 67 All these findings indicate that the RUNT domain is involved in melanoma metastasis and cell migration. RUNX2 can reactivate the MAPK and PI3K/AKT pathways, thereby endowing melanoma cells with high metastatic potential.…”
Section: The Transcription Factor Runx2 and Malignant Tumorsmentioning
confidence: 93%
“… 66 RUNT domain promotes bone metastasis of melanoma cells through the complex interactions with genes involved in bone remodeling through the ERK/p-ERK and AKT/p-AKT pathways. 67 All these findings indicate that the RUNT domain is involved in melanoma metastasis and cell migration. RUNX2 can reactivate the MAPK and PI3K/AKT pathways, thereby endowing melanoma cells with high metastatic potential.…”
Section: The Transcription Factor Runx2 and Malignant Tumorsmentioning
confidence: 93%
“…The ten most enriched known motifs identified by HOMER software are listed in Figure 4B . Among these enriched motifs, Runx2 was of particular interest because substantial in vivo and in vitro studies have shown that this gene is strongly associated with osteogenesis ( Tosa et al, 2019 ; Deiana et al, 2020 ). This suggested that Dlx2 may function in collaboration with Runx2 to reshape the transcriptome when Dlx2 is overexpressed.…”
Section: Resultsmentioning
confidence: 99%
“…RUNX2 can also be regulated post‐transcriptionally and we recently demonstrated that RUNX2 protein levels are increased in miR‐204‐silenced MSCs during the middle phase of osteogenic differentiation 17 . Moreover, using melanoma cells KO for the RUNT domain of RUNX2, we demonstrated that the RUNT domain plays an important role in the modulation of the expression of genes involved in bone metastases 18 …”
Section: Introductionmentioning
confidence: 85%
“…17 Moreover, using melanoma cells KO for the RUNT domain of RUNX2, we demonstrated that the RUNT domain plays an important role in the modulation of the expression of genes involved in bone metastases. 18 The present work, therefore, contributes to the understanding of FBXW11 role in osteogenic cells by evaluating its modulation both during osteogenic commitment and in altered osteoblastic cells characterized by RUNX2 mutations or resulting from tumour transformation.…”
mentioning
confidence: 94%